Analisis Kolaborasi Penelitian Ilmiah Dosen Fakultas X dengan Social Network Analysis (SNA) - Hennie Tuhuteru; Ade Iriani (Maranatha University Press, 2018)
Scientific publications have become the benchmarks of a country’s progress in the field of academics. This prompted the Indonesian government to issue a policy, to increase the researcher’s interest in collaborating and publicizing their research. Improving quality in research collaboration at college or faculty level could be done by analyzing the research collaboration conducted before. This research aims to understand the pattern of research collaboration, conducted by lecturers of Faculty X in YZ University based on the published scientific papers both locally, nationally and internationally. The method used to analyze the collaboration is Social Network Analysis (SNA). The centralizes measure that we used in SNA are degree centrality, closeness centrality, and betweenness centrality, to know how big the influences of each actor in the network. Additional attributes used to understand collaboration patterns, i.e. Study Program and Academic Functional Position (JAFA). The results of this research are the centrality value of each actor and the mapping of the network pattern based on the centrality and the attributes used. In addition, the relationship between actors is also seen based on the attributes that have been determined so as to provide more views on the conclusions of this study. It could be concluded that with the measurement in SNA, could be found the pattern of collaboration research from each actor based on the measurements of social network in the form of sociogram and the result of analysis of each actor in the form of sociometry.